2010
DOI: 10.1590/s1984-82502010000300016
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, analgesic and anti-inflammatory activities of Leucas cephalotes (Roxb.ex Roth) Spreng

Abstract: The whole plant of the methanolic extract from Leucas cephalotes was screened for in vitro antioxidant (using the DPPH method), in vivo analgesic (using hot plate test in mice) and anti-inflammatory (using rat paw edema test) activities. The methanolic extract of Leucas cephalotes (MELC) scavenged the DPPH radicals in a dose-dependent manner. The IC 50 value to scavenge DPPH radicals was found to be 421.3µg/ml. A significant (p<0.0005) analgesic activity was observed at 60 min with 200 mg/kg, and 400 mg/kg exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Our results corroborated with the study conducted by Yadav et al, (2012[ 23 ]) where non-polar fraction of methanolic extract of L. cephalotes significantly reduced the increased levels of TNF-α, IL-1β and IL-6 in mouse ear tissue homogenate. Baburao et al (2010[ 1 ]) also reported that at doses of 200 and 400 mg/Kg body weight p. o methanolic extract of this plant demonstrated an anti-inflammatory activity in a carrageenan induced rat paw edema model. Hence, it can be estimated that mostly the non-polar components viz .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results corroborated with the study conducted by Yadav et al, (2012[ 23 ]) where non-polar fraction of methanolic extract of L. cephalotes significantly reduced the increased levels of TNF-α, IL-1β and IL-6 in mouse ear tissue homogenate. Baburao et al (2010[ 1 ]) also reported that at doses of 200 and 400 mg/Kg body weight p. o methanolic extract of this plant demonstrated an anti-inflammatory activity in a carrageenan induced rat paw edema model. Hence, it can be estimated that mostly the non-polar components viz .…”
Section: Resultsmentioning
confidence: 99%
“…Considering the anti-inflammatory potential of Leucas cephalotes and its related species viz. Leucas aspera (Kripa et al, 2011[ 14 ]; Baburao et al, 2010[ 1 ]), we evaluated previously the dichloromethane (LCD), ethyl acetate (LCE) and methanol extracts (LCM) of this plant for in vitro pro-inflammatory cytokines (TNF-α and IL-1β) and nitric oxide (NO) inhibition in RAW 264.7 cells. Results revealed that LCD exhibited significant inhibition of NO, TNF-α and IL-1β production with an IC 50 of 49.3, 46.8 and 49.8 µg/mL respectively as compared to LCE and LCM (IC 50 = 50 to > 100 µg/mL) (Patel et al, 2014[ 19 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Lamiaceae Whole plant Antidote, jaundice, inflammation, asthma, fever, cough, malaria, anemia and sexual weakness in male [11,89] Anti-inflammatory [92,[94][95], analgesic [94], antioxidant [96][97], antimicrobial [98][99][100][101], antifilarial [102], antifertility [103], antiplasmodial [104], hepatoprotective [105], and antidiabetes activities [93,106] 12. Millingtonia hortensis L.f.…”
Section: Stemona Burkilliimentioning
confidence: 99%
“…Verma et al studied the fatty acid content of all parts of L. cephalotes by GC/MS and reported the presence of caprylic acid, capric acid, lauric acid, azelaic acid, myristic acid, palmitic acid, palmitoleic acid, margaric acid, oleic acid, linoleic acid, linolenic acid, arachidic acid, behenic acid, tricosanoic acid, lignoceric acid, pentacosanoic acid, cerotic acid, montanic acid, melissic acid [93]. Many biological/pharmacological investigations have demonstrated that, potentially, L. cephalotes has many valuable applications such as anti-inflammatory [92,[94][95], analgesic [94], antioxidant [96][97], antimicrobial [98][99][100][101], antifilarial [102], antifertility [103], antiplasmodial [104], hepatoprotective [105], and antidiabetic remedy [93,106]. Millingtonia hortensis L.f.: M. hortensis, a member of the family Bignoniaceae, is widely distributed and cultivated in many Asian countries.…”
Section: Gaultheria Fragrantissimamentioning
confidence: 99%
See 1 more Smart Citation